ПОНЯТТЯ ТА ВИДИ ПРИНЦИПІВ ЗАБЕЗПЕЧЕННЯ ІНФОРМАЦІЙНОЇ БЕЗПЕКИ В ЗБРОЙНИХ СИЛАХ УКРАЇНИ - Буга, Леся Василівна (SUPREMANCE OF LAW, 2018)
In the article, based on the analysis of scientific views of scientists, the theoretical approaches to the definition of such concepts as “principle” and “principles of law” are researched. Author’s definition of the concept of “principles of information security in the Armed Forces of Ukraine” is provided. The classification of such principles is carried out, and is divided into two main groups: general law and special. Th e necessity to consolidate the principles of information security in the Armed Forces of Ukraine at the legislative level is emphasized.